2020
DOI: 10.1073/pnas.1915773117
|View full text |Cite
|
Sign up to set email alerts
|

Circadian control of interferon-sensitive gene expression in murine skin

Abstract: The circadian clock coordinates a variety of immune responses with signals from the external environment to promote survival. We investigated the potential reciprocal relationship between the circadian clock and skin inflammation. We treated mice topically with the Toll-like receptor 7 (TLR7) agonist imiquimod (IMQ) to activate IFN-sensitive gene (ISG) pathways and induce psoriasiform inflammation. IMQ transiently altered core clock gene expression, an effect mirrored in human patient psoriatic lesions. In mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 48 publications
(56 reference statements)
3
62
0
Order By: Relevance
“…The results revealed that CDK1 protein was overexpressed (positively intense stained) in psoriatic skin lesions as compared to non-lesional areas. This observation was consistent with that in the study by Greenberg et al (2020) ( 63 ), who reported an increased CDK1 expression in psoriatic lesions. The psoriasis skin lesions and non-lesional skins were assessed for the expression and localization of CDH1.…”
Section: Discussionsupporting
confidence: 93%
“…The results revealed that CDK1 protein was overexpressed (positively intense stained) in psoriatic skin lesions as compared to non-lesional areas. This observation was consistent with that in the study by Greenberg et al (2020) ( 63 ), who reported an increased CDK1 expression in psoriatic lesions. The psoriasis skin lesions and non-lesional skins were assessed for the expression and localization of CDH1.…”
Section: Discussionsupporting
confidence: 93%
“…This suggested to us that an unknown, non-canonical pathway from IFN-γ to the clock was active. During the revision of this manuscript, a study provided evidence that imiquimod, through TLR7, triggers IFN regulatory factor 7 (Irf7) in mouse skin and also suppresses several core clock genes (65). Given that multiple pro-inflammatory stimuli were able to suppress PER2 LUC , it is tantalizing to speculate that there may be a common player, such as Irf7, related to all of these stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the disruption of circadian rhythms has been suggested to lead to the impairment of innate immunity 26 - 28 . In particular, mice lacking circadian rhythms showed robust activation of the IFN pathway 27 , and the circadian clock has been shown to regulate cellular susceptibility to the herpes and influenza viruses 29 . A recent study revealed that systemic Bmal1-knockout (KO) mice had an exacerbated imiquimod-induced ISG response in the skin and isolated epidermis, suggesting an involvement of the circadian clock in the innate antiviral response 27 .…”
Section: Discussionmentioning
confidence: 99%